2021
DOI: 10.5114/ada.2021.108930
|View full text |Cite
|
Sign up to set email alerts
|

Syphilis: then and now

Abstract: Getting to know the history of syphilis should begin with an attempt to establish the original source of its spread throughout the world. The dispute about the origin of syphilis, a sexually transmitted infection caused by Treponema pallidum (subspecies pallidum), had not been resolved even as late as in the twenty-first century, and to this day the supporters and opponents of the thesis that syphilis was brought to Europe by Christopher Columbus’ sailors have been fighting without solid and sustainable founda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
4
0
4
Order By: Relevance
“…Although syphilis can present with a variety of manifestations (leading to it being nicknamed ‘the great imitator’), 2 it can be divided into four stages: primary, secondary, latent and tertiary. All stages of syphilis require treatment 3 . We present a rare case of tertiary syphilis in our clinical practice.…”
Section: Figurementioning
confidence: 93%
See 2 more Smart Citations
“…Although syphilis can present with a variety of manifestations (leading to it being nicknamed ‘the great imitator’), 2 it can be divided into four stages: primary, secondary, latent and tertiary. All stages of syphilis require treatment 3 . We present a rare case of tertiary syphilis in our clinical practice.…”
Section: Figurementioning
confidence: 93%
“…All stages of syphilis require treatment. 3 We present a rare case of tertiary syphilis in our clinical practice.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…As localizações das lesões desse estágio da doença são geralmente em genitália, mas pode ocorrer em região perianal, lábios, língua, mucosa oral, gengiva, faringe, amígdalas e dedos. Associado ao quadro cutâneo, pode ocorrer linfadenomegalia regional por várias semanas, caracterizada por linfonodos endurecidos, bem delimitados, indolores, fibroelásticos e móveis (KATARZYNA PLAGENS-ROTMAN et al, 2021;KHAN et al, 2023).…”
Section: Manifestações Clínicas Da Sífilis Primária Secundária Latent...unclassified
“…In recent years, the incidence of syphilis has been on the rise in Poland and globally, which is probably related to the higher number of risky sexual encounters with random people, especially among homosexual men (MSM—men who have sex with men) [ 4 , 5 ]. The most common way syphilis is spread is through sexual contact (sexual intercourse, kisses) when the bacteria enter the body through mucus membranes or broken skin [ 6 ]. A study published in the Journal of the American Medical Association (JAMA) in 1971 showed that during 30 days of observation the risk of becoming infected with syphilis through sexual contact with an infected person is 30% [ 7 ].…”
Section: Introductionmentioning
confidence: 99%